The role of calcium phosphates and silicates in the storage and transport of phosphorus at the upper-to-lower mantle transition: an experimental study to 25 GPa in a model peridotitic bulk composition - Pausch, Tristan; Joachim-Mrosko, Bastian; Withers, Anthony C.; Ludwig, Thomas; Vazhakuttiyakam, Jaseem; Konzett, Jürgen (Geochimica et cosmochimica acta, 2024)
Calcium (Ca) phosphates are major hosts for phosphorus, halogens and incompatible trace elements in the Earth’s crust and mantle and, by supplying almost all phosphorus to the biosphere, are indispensable for sustaining life on Earth. To better understand the role of Ca-phosphates in the deep silicate Earth portion of the global phosphorus cycle at depths of the transition zone, we performed experiments in the P-T range of 15-25 GPa and 1600-2000 °C using a moderately fertile peridotite doped with 3 % synthetic β-Ca3(PO4)2 and 1 % of a trace element mix containing a range of HFSE, LILE, REEs, Cl and Br. Tuite is stable to at least 25 GPa at which pressure its upper T-stability limit is between 1700 and 1750 °C. At 15 GPa, by comparison, the upper T-stability limit is located between 1750 and 1800 °C, indicating a negative slope of the tuite-out reaction(s). Thus, tuite is stable to at least 700-km depth with a maximum T-stability close to or slightly above the average current mantle adiabat (ACMA) at 20-25 GPa and significantly above the ACMA at 15 GPa. Beyond the P-T stability limit of majoritic garnet, tuite is the principal subsolidus phosphorus carrier in the uppermost lower mantle. Beyond the P-T stability limit of tuite, phosphorus is likely to either (i) enter a Ca3(PO4)2 polymorph with an even higher density, (ii) form an entirely new phosphate phase or (iii) be accommodated in lower mantle silicates in six-fold coordination. Within the P-T range of our experiments, the phases encountered show the following trend of phosphorus contents:Pmelt>Pmajoritic garnet > Polivine ≅ Pringwoodite > Pdavemaoite ≅ Pwadsleyite > Pclinoenstatite ≅ Pbridgmanite ≅ Pferropericlase. Even when coexisting with tuite, bridgmanite and ferropericlase show phosphorus contents < 100 µg/g, and davemaoite has phosphorus contents that do not exceed 390 µg/g, testifying to the very limited phosphorus storage capacity of the lower mantle. Model calculations based on the phosphorus contents of ocean island basalts (OIBs) compared with those of mid ocean ridge basalts (MORBs) indicate that the OIB source is significantly richer in phosphorus than the MORB source and, for a wide range of OIB phosphorus contents, is likely to contain modal apatite. The relative importance of Ca-phosphates and silicates as phosphorus carriers in the peridotitic upper and uppermost lower mantle is strongly dependent upon pressure and the bulk phosphorus content. With increasing P, phosphorus is progressively transferred from Ca-phosphates to silicates with an ensuing decrease in the modal amount of the Ca-phosphates. Dependent upon the bulk phosphorus content, this may cause the Ca-phosphates to disappear before the upper-to-lower mantle boundary is reached, leaving majoritic garnet as the major phosphorus host. Breakdown of garnet will subsequently cause tuite to re-appear in the uppermost lower mantle and to resume its role of the principal subsolidus phosphorus carrier. For sufficiently high bulk phosphorus contents, tuite will remain stable throughout the transition zone, thereby maintaining phosphorus saturation in the coexisting silicates, and will eventually be joined by the tuite newly generated by garnet breakdown.
Online verfügbar: 26. April 2024, Artikelversion: 20. Mai 2024
Gesehen am 13.01.2025